Prevalence of Diabetic Foot Ulcers among People with Diabetes Mellitus - Francis, Daris; K., Kotteswaran; Pramod, P.V. (INTI International University, 2023)
Introduction: With 8.6% prevalence, India tops the list in terms of the burden of diabetes. A major complication of diabetes mellitus is diabetic foot ulcer, which affects type 2 diabetes more frequently. This study's objective was to determine the prevalence and risk variables that contribute to the development of diabetic foot ulcers. Method: A hospital-based cross-sectional survey was conducted with 108 type 2 diabetic patients who were chosen from the outpatient department of a major diabetic care facility. The socio-demographic data was gathered. The clinical biochemistry lab attached to the hospital performed the measurements of biochemical variables. The Wagner Meggitt Classification was used to stage each patient's diabetic foot. Results: Prevalence of Diabetic Foot Ulcer was 10.2%. Grade III was the most prevalent stage of presentation, followed by Grade IV according to classification system by Wagner Meggitt. No significant correlation between the DFU group and other metabolic parameters such hypertension, retinopathy, neuropathy, HbA1c, cholesterol, HDL, and LDL were discovered. Conclusions: There were 10.2% of diabetic individuals presented with foot ulcers. Diabetes related foot ulcers were more common in males with an average age of 56.08± 0.69 years.